Pemuridan dan Dampaknya terhadap Etos Kerja Alumni Kristen di Kota Palu - Mertayasa, Nyoman; Sunkudon, Pieter (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
This study aims to measure the influence of discipleship on the work ethic and work discipline of Christian alumni in Palu City. Using a quantitative approach, data were collected through a closed-ended Likert-scale questionnaire from 65 respondents, who were selected based on the criterion of having participated in a discipleship programme for at least one year. A simple linear regression analysis was conducted to examine the relationship between discipleship and both work ethic and work discipline. The regression results indicate that discipleship has a significant impact on work ethic (R² = 39.3%) and work discipline (R² = 38.1%). Discipleship helps alumni perceive work as an act of worship to God and encourages the application of Christian values in the workplace, such as integrity, responsibility, and discipline. The implications of this study highlight the need for the development of more holistic discipleship programmes by integrating professional skills training to better equip alumni for workplace challenges. Additionally, this study encourages further exploration of other factors influencing the work ethic and discipline of Christian alumni.